(3ETcGdjI Sdhc GdESJbhGA aj eOGQS efWbI YGdjg hYdGbJg HeJZjQj GdYeQ hGdLfSs - (3jMjG, QfOi fHjgs ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3cdjI GdBOGHs, 2013)
(3JgOa gPg GdOQGSI Edi(B: 1) (3JSdjW GdVhA Ydi XGgQI GdJfeQ Ch GdGSJbhGA heYQaI CTcGdg (B((3daXj, LSOj Ch GfaYGdj(B) (3heOi GfJTGQg aj HYV GdeOGQS GdNGUI hGdQSejI aj efWbI YGdjI(B. 2) (3GdJYQa Ydi GdaQhb aj GfJTGQ gPg GdXGgQI JHYkG dcd ef eJZjQj GdLfS hGdYeQ(B. 3) (3ebGQfI GdfJGFL eG Hjf GdeOGQS GdQSejI hGdNGUI(B. 4) (3EecGfjI GNJdGa GdeQLYjI dMd gPg GdeTcdI eG Hjf GdeOGQS GdNGUI hGdQSejI eKd eQHj(B/(3I GdUa, GdfGXQ(B/(3I, GdeQTO(B/(3I, GdeYde(B/(3I, GdCgd(B. (3JYJeO GdOQGSI GdefgL GdhUaj, hJchfJ GdYjfI ef (B160 (3WGdHkG hWGdHI ef WdGH GdeQMdI GdeJhSWI ddUaha (B((3GdSGHY hGdKGef(B) (3ddYGe GdOQGSj (B2009- 2010(3, EfbSehG Edi (B80 (3ef GdeOGQS GdQSejI, h(B80 (3ef GdeOGQS GdNGUI(B. (3Je JWHjb gPg GdYjfI GSJHGfI ChdhjS ddGSJbhGA Ydi gPg GdYjfI, cCOGI dLeY GdeYdheGJ(B. (3JhUdJ GdOQGSI Edi GdfJGFL GdJGdjI(B: 1) (3JhLO aQhb aj Sdhc GdGSJbhGA GdLSOj JYRi Edi eJZjQ GdLfS hcGfJ GdfSHI GdCYdi ddPchQ(B. 2) (3gfGc aQhbGJ eG Hjf GdUa GdSGHY hGdUa GdKGef ajXgQ HhVhM hLhO aQhb aj Sdhc GdGSJbhGA JYRi deJZjQ GdUa, MjK cGf Hcd CTcGdg HfSHI CYdi aj GdUa GdSGHY(B. 3) (3Ef GfJTGQ Sdhc GdGSJbhGA HcGaI CTcGdg XgQ HTcd CcHQ aj GdeOGQS GdQSejI(B.s
(3GdfhY (B: (3QSGdIs
Keywords: Behavioral & Psychological disorder Gender; Sexe; Troubles Comportementales et Psychologiques; (3GdGVWQGHGJ GdfaSjI hGdSdhcjI GdLfOQs; (3YGdjgs